Inspection supervision as an instrument to fight against undeclared work in domestic and International law - Lipovčić Sanja Z. (Strani pravni život, 2019)
The paper analyses the notion of undeclared work, its manifestation forms, with an overview of circumstances that affect its occurrence. Also, the author gives an overview of International Labour Organization standards, principles and guidelines in relation to inspection supervision, and an overview of an international framework for the implementation of inspection supervision and references that it provides as a basis for suppressing undeclared work. Considering the current situation in the labour inspection, the established ILO standards on the work of labour inspection, as well as a range of available legal options aimed at suppressing undeclared work, it is indicated that the proposed organizational, personnel and technical changes in the governmental body itself shall contribute to the suppression of the observed social phenomenon.